Assessing the stability of azopolymer nanotopography during live-cell fluorescence imaging - Abdelrahman, Mona H.; Shen, Jerry; Fisher, Nicholas C.; Losert, Wolfgang; Fourkas, John T. (Frontiers in Bioengineering and Biotechnology, 2024)
Photomodifiable nanotopographies are a powerful means of gaining insight into how cells adapt to rapid changes in their physical microenvironment. Here we investigate the feasibility of performing live-cell fluorescence imaging on photoresponsive azopolymer nanotopography. In particular, we investigate the range of imaging parameters that can be used without photomodifying the nanotopography. Previous research in this area has focused predominantly on fluorescence imaging of stained, fixed cells on azopolymer nanotopgraphies that were photomodified while the cells were still alive. The few studies that have explored live-cell imaging used excitation in the red region of the visible spectrum to prevent photomodification of the azopolymer. We examined the response of azopolymer nanoridges over the entire wavelength range available on a spinning-disk confocal microscope, as well as a broad range of near-infrared wavelengths on a 2-photon microscope. In the former case, we find that no photomodification occurs under a broad range of constant scan-rate, power, and exposure-time conditions, with the exception of slight buckling observed after irradiation with a 514-nm laser at relatively high exposure. These imaging conditions were selected to replicate those employed for imaging of MCF10A epithelial cells, which are slow-moving cells requiring a typical frame rate of 1 frame/10 sec for optimal imaging. Higher powers and scan rates resulted in photomodification for a 514-nm laser, and a less pronounced effect for a 561-nm laser, but not for any other wavelength that we explored. For the latter case, 700-nm and 725-nm excitation were found to cause photomodification, but excitation at wavelengths ranging from 750 nm to 900 nm did not affect the azopolymers. As a proof of concept, we used Dictyostelium discoideum cells as a dynamic model system to demonstrate live-cell confocal fluorescence imaging at two different excitation wavelengths: 561 nm at low scan rate for fluorescence imaging, and 514 nm at higher scan rate for modification of the nanotopography. The reciprocity of the exposure of azopolymer nanotopgraphy for 1-photon exposure was also assessed using circularly-polarized light, and showed a consistent response across a broad range of combinations of power and exposure time with a constant exposure dose.